Molecular orientation of organic thin films on dielectric solid substrates: a phase-sensitive vibrational SFG study1. Issue 27 (21st July 2015) - Ge, Aimin; Peng, Qiling; Qiao, Lin; Yepuri, Nageshwar R.; Darwish, Tamim A.; Matsusaki, Michiya; Akashi, Mitsuru; Ye, Shen
<x xml:space="preserve">Abstract</x> Phase-sensitive SFG spectroscopy is employed to determine the absolute molecular orientation on the solid/air and solid/liquid interfaces.